Modification of carbon nanotubes by a novel biomimetic approach towards the enhancement of the mechanical properties of polyurethane. (1st June 2016) - Mu, Chenzhong; Zhang, Liying; Song, Yujie; Chen, Xuelong; Liu, Ming; Wang, Fuke; Hu, Xiao
Abstract: Polyurethane (PU) nanocomposites incorporated with polydopamine treated carbon nanotubes (PDA-CNTs) were prepared by solution casting method via in-situ polymerization, achieving excellent CNTs dispersion in the PU matrix. It was observed that, with a loading of only 0.3 wt%, the tensile modulus and tensile strength were increased by 40% and 100% respectively. This reinforcement even exceeded the predicted modulus by Halpin–Tsai model. It indicates extremely enhanced interfacial interaction between the fillers and the matrix. More interestingly, it was found that the incorporation of PDA-CNTs caused a significant change in the degree of phase separation in the PU matrix leading to a unique network-like structure which is responsible for the unexpected reinforcement effect. This understanding combining with the synthetic approach should be useful for future design of PU/CNTs nanocomposites for wide range of applications. Graphical abstract: Highlights: Pristine CNTs was successfully modified by PDA through self-oxidative polymerization. The PDA coating facilitated uniform CNTs dispersion in PU matrix and created strong interfacial interaction between them. PDA-CNTs increased the phase separation and induced a structural change of PU. 40% increase in tensile modulus and 100% increase in tensile strength were achieved withonly 0.3 wt% PDA-CNTs. The reinforcement by PDA-CNTs exceeded the modulus predicted by Halpin–Tsai model by ∼29% at 0.3 wt% of PDA-CNTs loading.